Reactivity of 4Fe+(CO)n=0–2 + O2: oxidation of CO by O2 at an isolated metal atom. Issue 13 (9th March 2017) - Ard, Shaun G.; Martinez, Oscar; Brown, Steven A.; Sawyer, Jordan C.; Armentrout, P. B.; Viggiano, Albert A.; Shuman, Nicholas S.
Abstract : The kinetics of Fe + (CO) n + O2 yield insight on the mechanism of O2 bond cleavage and CO oxidation occurring at a single non-noble metal atom. Abstract : The kinetics of 4 Fe + (CO) n =0–2 + O2 are measured under thermal conditions from 300–600 K using a selected-ion flow tube apparatus. Both the bare metal and n = 2 cations are inert to reaction over this temperature range, but 4 Fe + (CO) reacts rapidly ( k = 3.2 ± 0.8 × 10 −10 cm 3 s −1 at 300 K, 52% of the collisional rate coefficient) to form FeO + + CO2 . This is an example of the oxidation of CO by O2 occurring entirely on a single non-noble metal atom. The reaction of the bare metal reaction is known to be endothermic, such that this result is expected; however, the n = 2 reaction has highly exothermic product channels available, such that the lack of reaction is surprising in light of the n = 1 reactivity. Stationary points along all three reaction coordinates are calculated using the TPSSh hybrid functional. These surfaces show that the n = 1 reaction is an example of two-state reactivity; the reaction proceeds initially on the sextet surface over a submerged barrier to a structure with an O–O bond distance longer than that in O2, but must cross to the quartet surface in order to proceed over a second submerged barrier to rearrange to form CO2 . The n = 2 reaction does not proceed because, on all spin surfaces, the transition state corresponding to O–O separation is at higher energy than the separated reactants. The difference between the n = 1 and n = 2 reactions is not a result of steric effects, but rather because the O2 is more strongly bound to Fe in the entrance well of the n = 1 case, and that energy is available to overcome the rate-limiting barrier to O–O cleavage. Experimental verification of some of these details are provided by guided ion beam tandem mass spectrometry results. The kinetic energy dependence of the n = 1 reaction shows evidence for a curve crossing and yields relevant thermochemistry for competing reaction channels.